Apakah Produk Bank Syariah Indonesia Menarik Minat Masyarakat? - Nurhayati Nurhayati; Niar Astaginy; Ismanto Ismanto (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to: (1) Examine the effect of brand image on the intention to purchase Bank Syariah Indonesia KCP Kolaka products. (2) Assess the impact of religiosity on the intention to purchase Bank Syariah Indonesia KCP Kolaka products. The research uses an explanatory quantitative approach, including data collection through observation, documentation, and questionnaires. The study covers all residents of Kolaka Regency, with a sample size of 130 respondents selected through purposive sampling. Validity and reliability of research instruments were ensured using SPSS 25.0. Data analysis employed Structural Equation Modeling (SEM) based on Partial Least Square (PLS), with Smart PLS 4.0 used to test the measurement model and the structural model. The findings highlight a positive and significant influence of brand image on product intention, along with a similar positive and significant impact of religiosity on product inclination.